2011
DOI: 10.1038/ncb2164
|View full text |Cite
|
Sign up to set email alerts
|

Conversion of mouse fibroblasts into cardiomyocytes using a direct reprogramming strategy

Abstract: Here we show that conventional reprogramming towards pluripotency through overexpression of Oct4, Sox2, Klf4 and c-Myc can be shortcut and directed towards cardiogenesis in a fast and efficient manner. With as little as 4 days of transgenic expression of these factors, mouse embryonic fibroblasts (MEFs) can be directly reprogrammed to spontaneously contracting patches of differentiated cardiomyocytes over a period of 11-12 days. Several lines of evidence suggest that a pluripotent intermediate is not involved.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

19
530
3
10

Year Published

2012
2012
2019
2019

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 586 publications
(570 citation statements)
references
References 36 publications
19
530
3
10
Order By: Relevance
“…In contrast, we believe that lineage reprogramming using target cell-type-specific transcription factors represents direct conversion (i.e., transdifferentiation) without involving an intermediate pluripotent state. Consistent with this hypothesis, c-Myc was required for the dedifferentiation approach (21), presumably because without c-Myc the induction of pluripotency is decreased by orders of magnitude (31,32), and cell types representing a different germ layer, such as cardiomyocytes, can be achieved from a similar transient pluripotent state (20). Future studies will be required to determine whether specific NPC populations with defined differentiation potential, as shown here, can be generated using the transient dedifferentiation approach.…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…In contrast, we believe that lineage reprogramming using target cell-type-specific transcription factors represents direct conversion (i.e., transdifferentiation) without involving an intermediate pluripotent state. Consistent with this hypothesis, c-Myc was required for the dedifferentiation approach (21), presumably because without c-Myc the induction of pluripotency is decreased by orders of magnitude (31,32), and cell types representing a different germ layer, such as cardiomyocytes, can be achieved from a similar transient pluripotent state (20). Future studies will be required to determine whether specific NPC populations with defined differentiation potential, as shown here, can be generated using the transient dedifferentiation approach.…”
Section: Discussionmentioning
confidence: 72%
“…Following the seminal work of induced pluripotent stem (iPS) cell reprogramming (19), it was shown that transient expression of the four iPS cell reprogramming factors Oct4, Sox2, Klf4, and c-Myc followed by treatment with specific media succeeded in generating both cardiomyocytes and neural precursor cell (NPC) populations from fibroblasts (20,21). However, in these experiments the NPCs were generated with low efficiency (presumably because of inefficient induction of pluripotency and the stochastic nature of differentiation), the described cells could not self-renew, and the NPCs apparently lacked the ability to differentiate into oligodendrocytes.…”
mentioning
confidence: 99%
“…For example, during dedifferentiation, the addition of a JAK inhibitor can inhibit long-term expression of exogenous transcription factors including Oct-4, Sox2, Klf4 and c-Myc, which will block further dedifferentiation from an unstable intermediate to an iPS cell [24]. Small molecules have an enormous potential to facilitate the application of lineage reprogramming.…”
Section: Application Prospects Of Lineage Reprogrammingmentioning
confidence: 99%
“…The use and combinations of iPS reprogramming factors are not the same for distinct target cells. For example, forced expression of a single transcription factor, Oct-4, allows the generation of an intermediate population that gives rise to blood lineages [22], whereas at least three factors including Oct-4, which is indispensable, are required for cell conversion to cardiac and neural cells [24,25]. However, Their et al [26] reported that constitutive induction of Sox2, Klf4, and c-Myc while strictly limiting Oct-4 activity to the initial phase of reprogramming allows the generation of stably expandable neural stem cells (NSCs).…”
Section: Dedifferentiationmentioning
confidence: 99%
“…Some pluripotency factors used to produce iPSC can directly reprogram some cell types such as cardiomyocytes (Efe et al, 2011), neural stem cells or progenitors , angioblast-like progenitor cells (Kurian et al, 2013), endothelial cells (Li et al, 2013a), pancreatic lineages , and hepatocytes . Ma et al (2013) showed that pluripotent factors can reprogram adult cells into pluripotent cells with multiple steps and that at certain steps some cells' fates are formed as transition stages of epigenetic reprogramming .…”
Section: Pluripotency Factors For Indirect Reprogrammingmentioning
confidence: 99%